Bis{N-[2-hydroxy-1,1-bis(hydroxymethyl)ethyl]glycinato-κ(3) O,N,O′}iron(II) - Jiang, Ning (International Union of Crystallography, 2014)
In the title compound, [Fe(C(6)H(12)NO(5))(2)], the Fe(II) ion lies on an inversion center and is coordinated by two N atoms and four O atoms from two tridentate N-[2-hydroxy-1,1-bis(hydroxymethyl)ethyl]glycine ligands, forming a slightly distorted octahedral coordination environment. In the crystal, O—H⋯O, O—H⋯N and weak C—H⋯O hydrogen bonds link molecules, forming a three-dimensional network.